Chapter 10 The European Green Deal and Public Procurement Law - Uysal, Ezgi; Janssen, Willem A. (Taylor & Francis, 2024)
Drawing on a range of expert contributions, this book explores how the European Green Deal is being deployed in practice and observes how the EU tries to promote the protection of the environment in third countries. This book begins by assessing the state of the art in terms of the key conceptual issues and analyses sectoral initiatives that are particularly relevant for the deployment of the European Green Deal external dimensions. These include the Carbon Border Adjustment Mechanism, the EU’s regulatory action in the control of maritime emissions, the 2030 Biodiversity Strategy, the Deforestation Initiative, the Zero Pollution Initiative, the From Farm to Fork Initiative, and the Climate Neutrality and Clean Energy Initiative in the context of the Energy Charter Treaty. Next, the authors deal with horizontal aspects of the European Green Deal that also have external dimensions, such as the Green Deal Diplomacy, the Green Public Procurement, funding measures, initiatives related to corporate sustainability and due diligence, and the implementation and enforcement of EU environmental law. This volume concludes with a cross-cutting analysis, focusing on how the EU can strengthen the impact of its normative power on international environmental governance, while also noting its limitations. Deploying the European Green Deal will be of great interest to students and scholars of international and EU environmental law and environmental policy and governance.